Futebol e controle do jogo: as interdependências do árbitro brasileiro na configuração VAR - Loureiro, Luiz Augusto Zafalon (2020)
Soccer is mediated by control devices such as rules, standards and institutionalized conduct, at first, by the Football Association (FA), then by the International Football Association Board (IFAB) and Fédération Internationale of Football Association (FIFA), institutions that have become globalized and regulators of world soccer. Each continent has its administrative and regulatory body, configurations and interdependencies, such as the Confederation of North, Central American and Caribean Association Football (CONCACAF) and Confederación Sul-Americana de Fútbol (CONMEBOL), in addition to national institutions, such as the Brazilian Football Confederation (CBF) and at local level the Paraná Football Federation (FPF). The soccer referee emerged and started his network of interdependencies from 1891 and his role is to control the game, safeguarding its characteristics and compliance with the rules, maintaining violence at socially acceptable levels, seeking fair play and good progress of the sporting spectacle within the spirit of the rules. The objective of this dissertation was to identify the interdependencies of the Brazilian referee and the VAR configuration in the control of professional soccer. Developed from a qualitative research, of a descriptive nature. For data collection, the interview method was used, through a questionnaire containing 10 open questions, created by the researchers and validated by four doctors with experience in qualitative research. The survey participants submitted to the questionnaire were 5 male referees who played in national and international games certified by the FPF, CBF and FIFA. For data analysis we used Lawrence Bardin’s Content Analysis method. In the process of reading and interpreting the results, we used Norbert Elias’s configurational theory. As a conclusion, we identified that the configuration of Brazilian soccer is in accordance with the globalized and contemporary interdependencies of world soccer and has singularities that differentiate it, related to the IFAB – FIFA Multiannual Strategic Planning, due to the advance in the adhesion and implementation of the new informational control technologies of the game, Information and Communication Technologies – ICTs, characterized by the VAR configuration, which reinforces the maintenance of the rules of the game, which were reconfigured in 2016 and established new interdependencies to the referee. As one of the first countries to adopt new technologies, Brazil has inserted new agents in the configuration of arbitration, with more precise technological devices in the control of the match, mitigating errors, injustices and unnecessary violence, which makes soccer sport an impulse to the civilizing process.